Pendampingan Implementasi Pembelajaran Berbasis Etnomatematika Pada Guru SMP Muhammadiyah 4 Malang - Yus Mochamad Cholily; Anis Farida Jamil; Mayang Dintarini (Universitas Serang Raya, 2024)
One keys to achieving learning objectives is designing meaningful learning for students. Meaningful learning is learning that can be related to students' daily lives. Based on the results of interviews with SMP Muhammadiyah 4 Malang, students felt that learning mathematics is not related to students' daily lives. Therefore, the team offers alternative meaningful learning solutions using an ethnomathematics approach. Ethnomatematics plays a role in connecting culture with mathematics. By using ethnomathematics it is hoped that students can also get to know their local culture and preserve regional culture, especially Malang. Implementation of community service activities through four stages, namely training teachers in exploring the culture of mathematical concepts, assisting in the development of ethnomathematics-based teaching materials, assisting in the implementation of ethnomathematics-based learning, and evaluating activities.